(untitled) (Bangladesh Medical Journal, 2014)
Troponin I (cTnI) isoform is cardiac muscle specific protein and shown to have several features as a preferred marker of myocardial injury. It rises early in acute myocardial infarction (AMI) and attains levels that are clearly separated from baseline values. It remains elevated for several days providing a long window for detection of cardiac injury. The objective of the study was to evaluate for the profile of cTnI level among symptomatic AMI patients. The study was conducted at National Institute of Cardiovascular Disease, Dhaka, Bangladesh from July 2007 to June 2008 and total 9552 patients with type 1 or type 2 MI were included. Blood Sample was taken within 3 days of symptoms and cTnI was measured by chemiluminescent immunometric assay method. cTnI was considered positive when the value was >1ng/ml and study population was divided as per age, sex and cTnI level. The mean (+ SD) age of all patients was 55(+ 12.8) years and majority was males (82.20%). Seasonal variation showed highest positive cases in winter. In case of circadian variation positive cTnI results were suggestive of morning peak of AMI. Positive results were obtained in 32.3% of Cases. cTnI is now considered as a better indicator of myocardial injury. Further study in depth is necessary to correlate with clinical symptoms and other diagnostic tests to make a complete profile of AMI according to the latest subtypes. DOI: http://dx.doi.org/10.3329/bmj.v42i1.18969 Bangladesh Med J. 2013 Jan; 42 (1): 3-6